Analisis Pelaksanaan Pembinaan Kemandirian di Lembaga Pemasyarakatan Perempuan Kelas II A Kota Palembang - Safitri, Leni; Lisdiana, Lisdiana; Novaria, Eva (@-Publik: Jurnal Administrasi Publik, 2024)
The research titled "Implementation of Independence Development in Class II A Women's Penitentiary Palembang" highlights two main issues: the lack of agricultural facilities within the institution and the low enthusiasm of inmates towards the independence development program. The research method applied is qualitative descriptive. Based on the conducted research, several key aspects in the development program at Class II A Women's Penitentiary Palembang are identified: Planning: Despite being supported by DIPA funds and Bayangkhari Polda grants, there are still deficiencies in facilities and land that affect the optimization of farming programs. Organization: The program operates effectively when all members clearly understand their roles and functions, enabling preparation and management of the program to be more measurable. Actuating: Implementing performance standards and delegation of authority help maintain coordination of tasks in accordance with established SOPs. Controlling: Overall, inmates participating in the independence development program are less motivated. This results in minimal skills upon their release, hence the impact of the development program is not yet significant. These findings underscore the importance of improvement in several aspects, particularly in providing facilities and infrastructure, as well as motivation for inmates to maximize the benefits of the development program they are involved in.